(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2026)
Abstract The objective of this research is to explore how the diphthong sounds influence the pronunciation students faculty of letters UMI in the academic year 2023- 2024 through the English Language Speech Assistant application and to investigate to what extent the diphthong sounds influence the pronunciation students faculty of letters UMI in the academic year 2023-2024 through the English Language Speech Assistant application. The researcher used a pre-experimental method design and collected data by giving pre-tests and post-tests. There were 17 students faculty of letters UMI in the academic year 2023-2024 involved in this study. The test conducted was to pronounce words consisting of 40 words in the pre-test and post-test. The results of the researcher showed that the English Language Speech Assistant (ELSA) application was significant in improving students’ pronunciation. This is because before using the English Language Speech Assistant (ELSA) application, the average score of students was 52.79, but after students used the ELSA application, the average score of students increased to 67.5 with a percentage increase of 27.86%. This significant increase occurred because Language Speech Assistant (ELSA) can help improve students’ pronunciation skills. Based on the result above, it can be seen that there is an improvement in students’ faculty of letters UMI especially in pronunciation.